European Consumers' Perceptions of Time–Temperature Indicators in Food Packaging. (22nd September 2014) - Pennanen, Kyösti; Focas, Caralampo; Kumpusalo‐Sanna, Vilja; Keskitalo‐Vuokko, Kaisu; Matullat, Imke; Ellouze, Mariem; Pentikäinen, Saara; Smolander, Maria; Korhonen, Virpi; Ollila, Margareetta
<x xml:space="preserve">Abstract</x> Food quality is an essential aspect of the food industry. Time–temperature indicator (TTI) technology has the capability to provide information on temperature fluctuations that temperature‐sensitive food products have undergone. However, the adoption of the TTI technology in the consumer market has yet to materialize despite the many benefits that TTIs bring to food manufacturers, retailers and consumers. One of the reasons for this could be the general lack of knowledge regarding consumers' perceptions of TTIs. The aim of this study is to understand the consumers' knowledge, interest and perceptions of TTIs. To reach this aim, 16 focus group discussions and a quantitative survey were conducted in four European countries (Finland, Greece, France and Germany) during May–October 2012. Consumers' views on both the TTI technology concept and two commercially available TTI applications were studied. The results of the study show that consumers in all countries appreciate and understand TTI technology and associate differing benefits with it, especially so in warmer countries. On the other hand, the studied applications did not meet all consumers' expectations implying the need for further work to enable TTIs to gain a wider acceptance. Copyright © 2014 John Wiley & Sons, Ltd.